Analisis Kesalahan Siswa dalam Menyelesaikan Masalah Open Ended Berdasarkan Teori Newman - Nabilah Mansur; Subanji Subanji (Al Hikmah: Journal of Education, 2021)
Analysis Of Students’ Error In Solving Problems Of An Open Ended Based On The Newman Theory. Abstract is The purpose of this research is to describe the types of students’ errors and find out the number of errors committed by students on each type of error in resolving the open ended problems. Classify the type of error based on Newman theory, which are error reading, understanding, transformation, process skills, and error writing answers. The subject of this research is from 30 students of VIII grade of SMPN 24 Malang. This research using data test collection techniques which is an open ended question on statistical material and interviews to obtain additional data. Data analysis was done by reduction, presentation, and conclusion. The result of the analysis obtained that the students’ error are reading errors, errors of understanding, transformation’s errors, process skills’ errors, and write response’s errorsPenelitian ini bertujuan untuk mendeskripsikan tipe-tipe kesalahan siswa dan mengetahui banyaknya kesalahan yang dilakukan siswa pada tiap tipe kesalahan dalam menyelesaikan masaalah open ended. Pengklasifikasian tipe kesalahan berdasarkan teori Newman, yaitu kesalahan membaca, memahami, transformasi, keterampilan proses, dan kesalahan penulisan jawaban. Subjek penelitian ini adalah siswa kelas VIII SMP Negeri 24 Malang yang berjumlah 30 orang. Penelitian ini menggunakan teknik pengumpulan data berupa tes yaitu soal open ended pada materi statistika dan wawancara untuk memperoleh data tambahan. Analisis data dilakukan dengan reduksi, penyajian, dan penyimpulan. Hasil analisis didapatkan bahwa kesalahan yang dilakukan siswa adalah kesalahan membaca, kesalahan memahami, kesalahan transformasi, kesalahan keterampilan proses, dan kesalahan penulisan jawaban.